Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2018)
To date, three nominal species of the eutheiine genus Paraneseuthia were known to occur in Japan (in Honshū and Kyūshū). A female of an undescribed species was also recorded from Iriomote Island of the Ryūkyū Archipelago. Two new species are here added to this list: P. ishigakianas p. n. (Ishigaki Is.) and P. ehimensis sp. n. (Shikoku). Paraneseuthia holzneri (Franz), described on the basis of a single male with erected and distorted aedeagus, is recorded from a new locality and its aedeagus is illustrated.